'People's Action Week' against the 6th Ministerial Conference of the WTO. Life jacket in which people are trying to reach the building where the conference was held
'People's Action Week' against the 6th Ministerial Conference of the WTO. Life jacket in which people are trying to reach the building where the conference was held.